Does Management Accounting Information Meet the Needs of SMEs? An Investigation of Its Usefulness from Manufacturing Enterprises - Lynn R. Legaspi, Joy (International Journal of Engineering and Technology, 2018)
The use of appropriate management accounting techniques for the problem at hand are useful to managers. This study describes the level of usefulness of management accounting tools (MATs) used, test the relationship of MATs used to net income and capital, test of difference between the level of its usefulness and the difficulties encountered in applying the tools. Questionnaire survey was used to obtain information from manufacturing sector. Frequency, median, Spearman Rho and Mann-Whitney U were utilized to analyze the data. The study suggest that medium firms utilized more tools than small enterprises. Statement of cash flow analysis, capital budgeting decisions and financial budgets were considered as the very useful tools used. Likewise, the study developed significant relationship between selected variables of size, level of net income and level of capital to the level of its usefulness for medium-sized enterprises and sufficient to create significant difference between the levels of its usefulness. Lack of qualified employees and its use are not deem necessary as to the nature of the enterprise operations ranked as the top barriers encountered in applying the tools. Therefore, the appropriateness of management accounting information depends upon the operating activities, strategies and the size of the organization.Â Â